Directed Motivational Currents: Using vision to create effective motivational pathways - Muir, Christine; Dörnyei, Zoltán (Zakład Filologii Angielskiej Wydział Pedagogiczno-Artystyczny Uniwersytetu im. Adama Mickiewicza w Kaliszu, 2013)
Vision, that is, the mental representation of the sensory experience of a future goal state (involving imagination and imagery), is currently at the forefront of motivational innovation, and in recent years it has been seen increasingly more often in the motivational tool kit of practicing language teachers. Theories such as Dörnyei’s L2 motivational self system have explored the power that creating effective visions can harness (see, e.g., Dörnyei & Kubanyiova, 2014) and when viewed in conjunction with other current research avenues, such as future time perspective and dynamic systems theory, vision offers exciting potential. A Di- rected Motivational Current is a new motivational construct that we suggest is capable of integrating many current theoretical strands with vision: It can be de- scribed as a motivational drive which energises long-term, sustained behaviour (such as language learning), and through placing vision and goals as critical cen- tral components within this construct, it offers real and practical motivational potential. In this conceptual paper, we first discuss current understandings of vi- sion and of Directed Motivational Currents, and then analyse how they may be optimally integrated and employed to create effective motivational pathways in language learning environments.
Keywords: Directed Motivational Current; vision; imagery; motivation process; L2 Motivational Self System; possible selves